Detección de anticuerpos totales para Covid-19 al personal docente, administrativo y estudiantil de la carrera de Laboratorio Clínico de la UNL - Riera Yanza, Jennifer Alexandra (2021)
Antibodies play important roles within the body against most infections. The kinetics of these during the Covid-19 disease can be determined by serological tests, which allows the detection of cases of infections with mild or no symptoms, the study of an outbreak or cluster in progress when the molecular tests are negative, and if there is a strong epidemiological relationship and clinical suspicion. Therefore, the present study aims to identify total antibodies, which means, defenses that the immune system generates when a human being suffers from an infection, for Covid-19 to the teaching, administrative, and student staff of the Clinical Laboratory career of the National University of Loja. This research is quantitative, with a non-experimental, cross-sectional, and descriptive design, which includes a population of 56 people. For this, the electrochemiluminescence method was used, and in this way , it was possible to determine the presence of IgG antibodies known also as immunoglobulins that offer protection against bacterial infections and viruses, and IgM defined as the first immunoglobulin that offers protection against infection, through a qualitative ELISA technique applied in cases positive for total antibodies, while identifying the frequency of total positive antibodies concerning the sex of the study population. Obtaining as results that 23% of the cases were positive and 76.8% negative for the presence of total antibodies, from which 100% presented IgG and only 30.8% IgM. In the same way, the male population showed a slightly higher frequency of total antibodies than the female. Keywords: SARS-CoV-2, total antibodies, IgG and IgM, ELISA, Electrochemiluminescence.